Analisis Faktor-Faktor yang Mempengaruhi Agresifitas Pajak (Tax Ag-gressiveness) Perusahaan yang Terdaftar di Bursa Efek Indonesia (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to explore the elements that influence the level of tax aggressiveness in companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Tax aggressiveness refers to the tax planning strategies undertaken by companies to reduce tax burdens through legal and illegal means. This study uses secondary data from the financial statements of manufacturing companies listed on the IDX for the period 2019-2023. The variables analyzed include company size, profitability, leverage, capital intensity, and institutional ownership. Tax aggressiveness is measured by the effective tax rate (ETR). The analysis method used is multiple linear regression with the help of SPSS software version 25. The results of the study indicate that company size and profitability have a significant negative impact on tax aggressiveness. Meanwhile, leverage shows a significant positive effect. On the other hand, capital intensity and institutional ownership do not show a significant impact on tax aggressiveness. This research contributes to policy makers' understanding of the elements that drive aggressive tax practices, so they can design more effective tax regulations.